Tourist Knowledge And Behaviours Towards Rabies Prevention–UBUD Bali Indonesia - I Nyoman Purnawan (Sean Institute, 2023)
Rabies is one of the causes of death in the world. Therefore rabies is a global health problem. In Ubud District, cases of Rabies Transmitting Animal Bites (GHPR) doubled compared to the previous year with the second highest average number of cases in Gianyar Regency. The GHPR case in Ubud does not only affect the local community but also some tourists who stay and vacation in Ubud. If this problem is not addressed it will have a direct impact on the decline of the tourism industry in Ubud. This research aims to obtain an overview of the level of knowledge and prevention behavior of tourists regarding rabies in Ubud as a tourist destination in Bali. This research is a descriptive study with a cross-sectional design. The sample for this research was 96 tourists who stayed and vacationed in Ubud, both domestic and international tourists. Data was collected through interviews with questionnaires and measurements then analyzed by univariate. The results of this research show that the majority of tourists already have high knowledge of rabies, namely 65% for international and 63% for domestic. As with knowledge, the majority of tourist prevention behavior is classified as good, namely 79% for international and 73% for domestic. It is recommended that the government and related agencies carry out policy improvements to increase public knowledge regarding changes in health behavior in terms of the use of information media to socialize the dangers of rabies to the public, especially the use of electronic media.